An in situ derived MOF@In2S3 heterojunction stabilizes Co(ii)-salicylaldimine for efficient photocatalytic formic acid dehydrogenation. Issue 51 (6th June 2022) - Zhang, Meijin; Lin, Wenting; Ma, Liang; Pi, Yunhong; Wang, Tiejun
Abstract : A hierarchical heterojunction with installation of in situ derived In2 S3 and [Co]-catalyst confined by salicylaldimine moiety significantly facilitates photocatalytic FA dehydrogenation. Abstract : We report here the hierarchical construction of a molecular Co(ii )-salicylaldimine catalyst and an in situ derived In2 S3 semiconductor in a MOF@In2 S3 heterojunction through sequentially controllable in situ etching and post-synthetic modification for photocatalytic hydrogen production from formic acid. The enhanced catalyst stability and facilitated charge carrier mobility between the In2 S3 photosensitizers and Co catalyst realize a superior H2 production rate of 18 746 μmol g −1 h −1 (selectivity > 99.9%) with a turnover number (TON) of up to 6146 in 24 h (apparent quantum efficiency of 3.8% at 420 nm), indicating a 165-fold enhancement over that of the pristine MOF. This work highlights a powerful strategy for synergistic Earth-abundant metal-based MOF photocatalysis in promoting H2 production from FA.